ANALISIS PERAN AKTOR DALAM IMPLEMENTASI PROGRAM KELURAHAN RAMAH LINGKUNGAN DI KECAMATAN BANYUMANIK - Ghana Abdila Hekmatyar; Kismartini Kismartini; R Slamet Santoso (Journal of Public Policy and Management Review, 2016)
Eco-Friendly Village program is the goverment’s efforts to manage and use space in order to improve health and society wealth to bring the city of Semarang clean , healthy , and green. Banyumanik as one of the programs target is one of the largest garbage contributor, this is because the district of Banyumanik located on the main road that caused the rapid development. This study aims to analyze the role of actors in the implementation of Eco-Friendly Village programme and to knows the determinants of the role of actors in the implementation of Eco-Friendly Village programme.This study is an qualitative descriptive study. Data was collected through observation, documentation, and in-depth interviews to informans who played a role in the program. The result of this study is there are some actors are involved in this program that is the goverments (Environment Agency, Banyumanik District, Srondol Kulon Village), NGO’s (PKK, Trash Bank “Resik Apik”), and society. Each actor have an important role that can help to achieve the objective of the program, although there were also actor with less contribution or their role are not maximum because of several factors that determine their role.Based on these results, the researcher suggest that of an improvement in the context of the role of each actors that involved, as well as improvement in the context of the determinants of the role of actors which are considered still unwell., so that the implementation of Eco-Friendly Village programme can run optimally.